S25 IL 17 production in primary and secondary Respiratory Syncytial Virus (RSV) infection and neutrophil transmigration. (16th November 2010) - Ugonna, K B; Plant, K; Everard, M L
Abstract : Introduction and Objectives: RSV causes winter epidemics of respiratory disease particularly in infants and the immunocompromised. Infected ciliated airway epithelial cells, local macrophages and dendritic cells secrete cytokines including interleukins (IL) 6 and 8, promoting a strong neutrophilic response that is important in disease clearance and airway inflammation. The IL 17 inflammatory pathway, which is important in surface immunity, has been little studied in RSV infection to date. The following hypothesis was explored: The IL17 pathway is important in neutrophil chemotaxis and restriction of RSV replication . Methods: A transwell model of the airway was devised, co-culturing A549s (an immortalised bronchial epithelial cell line) and neutrophils to study the effect of RSV and IL17 on the transmigration of neutrophils. Neutrophil transmigration was assessed using light microscopic immunocytochemistry. Nasal swabs were taken from infants with RSV positive Bronchiolitis (n=49), RSV negative Bronchiolitis (n=12), the symptomatic older siblings of RSV positive infants (n=15) and uninfected, asymptomatic children (n=20). Cytokines released (IL6/IL8/IL17a/IL21/TNF) were analysed by cytokine bead array. Results: IL 17 and RSV caused significantly increased number of neutrophils to transmigrate compared to either IL 17 or RSV alone. Primary RSV infections which caused hospitalisation, are characterised by high levels of nasal epithelial derived cytokines (IL 6, IL 8). Less severe secondary RSV infections are characterised by relatively low levels of IL 6 and IL 8 and relatively high levels of IL 17. Conclusions: There is evidence that IL 17 is synergistic with RSV induced IL 8 in promoting neutrophil transmigration in vitro . There is evidence to support IL 17 as an important cytokine restricting RSV production in secondary infection in vivo . This study suggests that the IL 17 pathway is important in the pathogenesis of RSV bronchiolitis and could be potentially important in the development of novel therapies for this ubiquitous and important cause of respiratory disease.